Topology Optimization of the Caudal Fin of the Three-Dimensional Self-Propelled Swimming Fish (Advances in Applied Mathematics and Mechanics, 2021)
Based on the boundary vorticity-flux theory,  topology optimizationof the caudal fin of the three-dimensional self-propelled swimming fishis investigated by combining unsteady computational fluid dynamics withmoving boundary and topology optimization algorithms in this study.The objective functional of topology optimization is the function of swimming efficiency, swimming speed and  motion direction control.The optimal caudal fin, whose topology is different from that of the natural fish caudal fin,makes the 3D bionic fish achieve higher swimming efficiency, faster swimming speedand better maneuverability.The boundary vorticity-flux on the body surface of the 3D fishbefore and after optimization reveals the mechanism of high performance swimmingof the topology optimization bionic fish.The comparative analysis between the swimming performance of the 3D topologyoptimization bionic fish and the 3D lunate tail bionic fish is also carried out,and the wake structures of two types of bionic fish show the physical naturethat the swimming performance of the 3D topology optimization bionic fish issignificantly better than the 3D lunate tail bionic fish.